1996
DOI: 10.1074/jbc.271.31.18588
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Prenyl Group on the G Protein γ Subunit in Coupling Trimeric G Proteins to A1 Adenosine Receptors

Abstract: The coupling of receptors to heterotrimeric G proteins is determined by interactions between the receptor and the G protein ␣ subunits and by the composition of the ␤␥ dimers. To determine the role of the ␥ subunit prenyl modification in this interaction, the CaaX motifs in the ␥ 1 and ␥ 2 subunits were altered to direct modification with different prenyl groups, recombinant ␤␥ dimers expressed in the baculovirus/Sf9 insect cell system, and the dimers purified. The activity of the ␤␥ dimers was compared in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
90
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 60 publications
10
90
1
Order By: Relevance
“…Although cross-linking studies have yet to detect receptor-␥ contact sites (7), several studies point to the importance of the carboxyl-terminal amino acid region and the type of prenyl group on the ␥ subunit in determining the interaction of the ␤␥ dimer with receptor (34,35). These latter studies may explain the lower reconstitutive activity of the ␤ 1 ␥ 1 dimer in the present study.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Although cross-linking studies have yet to detect receptor-␥ contact sites (7), several studies point to the importance of the carboxyl-terminal amino acid region and the type of prenyl group on the ␥ subunit in determining the interaction of the ␤␥ dimer with receptor (34,35). These latter studies may explain the lower reconstitutive activity of the ␤ 1 ␥ 1 dimer in the present study.…”
Section: Discussioncontrasting
confidence: 44%
“…In this regard, the ␥ 1 subtype sequence is the most divergent of those determined to date, and its lipid modification is a C-15 farnesyl group rather than the C-20 geranylgeranyl group found on most other ␥ subtypes (1). With regard to the latter, a recent study comparing ␤␥ dimers with the two types of prenyl groups showed that the wild type, geranylgeranylated ␥ 2 subunit and the mutant, geranylgeranylated ␥ 1 subunit had similar abilities to interact with the A 1 adenosine receptor (34). By contrast, the wild type, farnesylated ␥ 1 subunit and the mutant, farnesylated ␥ 2 subunit were much less effective.…”
Section: Discussionmentioning
confidence: 99%
“…Although the influence of the C-terminal sequences and the lipid modification of the γ-subunit on GPCR coupling has been described (56)(57)(58), our data indicate the influence of small differences in the sequence. Although the N-terminal sequences distinguish γ 9 , the C-terminal one-third of all three γ-subunits is highly similar (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 54%
“…The γ5-6G mutant was made to increase the distance between the geranylgeranyl modification on the Cys residue and the amino acid sequence at the C terminus previously identified as a contact site for the receptor [9]. Previous evidence from experiments with various receptors indicates that both the prenyl moiety and the C terminal amino acid sequence of the γ subunit are a requirement for receptor interaction of the G protein [13,14,30]. One possible reason for this requirement is that the receptor has contact sites for both the prenyl moiety and the C terminal residues.…”
Section: Mutations At the C Terminus Of The γ5 Subunit Induce βγ5 Tramentioning
confidence: 99%